Contested Policy of “Forest Areas with Special Management”: A Case Study of the Permit Holder in Kediri Regency, East Java - Listia Hesti Yuana; Suraya Abdulwahab Afiff (Jurnal Ilmu Kehutanan, 2025)
The Government of Indonesia introduced a Special Management Forest Areas policy to facilitate changes in forest governance in Java, particularly over approximately 1.1 million hectares of forestland that were previously under Perhutani's management. Therefore, this research aimed to examine the practical benefit of the policies for communities critically. The designation of forest communities as key stakeholders paradoxically risked further marginalization. This research applied a patchwork ethnography approach and relied on participant observation and in-depth interviews. Although Perhutani no longer held official authority, various strategies were implemented at site levels to maintain access to forest resources. During the transition period, forest communities struggled due to a lack of clear assistance. As a new actor, the Forestry Service Branch (CDK) could not provide intensive assistance because the communities had not yet undergone the transformation required to obtain legal recognition under the latest policies. The results showed that good intentions in policies to support marginalized communities were insufficient. For the purpose of justice, a strong commitment at the grassroots level was needed through intensive assistance to ensure that policies were not merely rhetorical but truly provided tangible benefits.